2020
DOI: 10.15252/embr.202050663
|View full text |Cite
|
Sign up to set email alerts
|

Male castration increases adiposity via small intestinal microbial alterations

Abstract: Castration of young males is widely used in the cattle industry to improve meat quality, but the mechanism linking hypogonadism and host metabolism is not clear. Here, we use metataxonomic and metabolomic approaches to evaluate the intestinal microbiota and host metabolism in male, castrated male (CtM), and female cattle. After pubescence, the CtM cattle harbor distinct ileal microbiota dominated by the family Peptostreptococcaceae and exhibit distinct serum and muscle amino acid profiles (i.e., highly abundan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 58 publications
(59 reference statements)
0
14
0
Order By: Relevance
“…The findings of this study demonstrate that an intact gut microbiome is required for skeletal muscle to fully adapt to exercise training. Additionally, the findings from this study add to the growing body of evidence supporting a gut microbiome-skeletal muscle axis (Bindels et al 2012;Fielding et al 2019;Lahiri et al 2019;Whon et al 2021). Future studies will seek to identify the bacterial species and associated metabolites that play a critical role in facilitating skeletal muscle hypertrophy and the fibre-type shift that occur in response to exercise with the expectation they will be unique for each of these processes.…”
Section: Discussionmentioning
confidence: 65%
“…The findings of this study demonstrate that an intact gut microbiome is required for skeletal muscle to fully adapt to exercise training. Additionally, the findings from this study add to the growing body of evidence supporting a gut microbiome-skeletal muscle axis (Bindels et al 2012;Fielding et al 2019;Lahiri et al 2019;Whon et al 2021). Future studies will seek to identify the bacterial species and associated metabolites that play a critical role in facilitating skeletal muscle hypertrophy and the fibre-type shift that occur in response to exercise with the expectation they will be unique for each of these processes.…”
Section: Discussionmentioning
confidence: 65%
“…In ruminants, a previous study found that anti- Porphyromonas gingivalis antibody titers were positively correlated with intramuscular adipose tissue content ( Watanabe et al, 2021 ). Castration in male cattle increased adiposity via small intestinal microbial alterations ( Whon et al, 2021 ), which resulted in a greater increase in the subcutaneous and intramuscular fat, and a higher meat tenderness score than those of non-castrated bulls ( Field, 1971 ; Marti et al, 2017 ). The castrated male cattle harbored distinct ileal microbiota dominated by the family Peptostreptococcaceae ( Whon et al, 2021 ).…”
Section: Gut Microbiota Affect Intramuscular Fat Depositionmentioning
confidence: 99%
“…Castration in male cattle increased adiposity via small intestinal microbial alterations ( Whon et al, 2021 ), which resulted in a greater increase in the subcutaneous and intramuscular fat, and a higher meat tenderness score than those of non-castrated bulls ( Field, 1971 ; Marti et al, 2017 ). The castrated male cattle harbored distinct ileal microbiota dominated by the family Peptostreptococcaceae ( Whon et al, 2021 ). Angus beef meat, which is superior in juiciness, tenderness, and flavor due to a higher intramuscular fat (IMF) content, was found to have a significantly higher relative abundance of Roseburia , Prevotella , and Coprococcus Angus ( Zheng et al, 2022 ).…”
Section: Gut Microbiota Affect Intramuscular Fat Depositionmentioning
confidence: 99%
“…Peptostreptococcaceae belonging to the order Clostridiales are a group of bacteria characterized by short chain fatty acid production in the process of degradation of plant-derived cellulose and hemicellulose components (Bernad-Roche et al, 2021). Previous studies demonstrated that the abundance of the family Peptostreptococcaceae in the gut microbiota of castrated bulls was higher than in uncastrated bulls, and they exhibited distinct serum and muscle amino acid profiles, with increased muscular fat storage (Whon et al, 2021).…”
Section: Composition Of Gut Microbiotamentioning
confidence: 99%
“…The differential MQTs between Angus cattle and Xinjiang brow cattle related to fat metabolism/deposition were found to be associated with the relative abundance of certain gut microbial genera, which could serve as potential gut microbial biomarkers to assist in improving meat quality of Xinjiang brow cattle. Whon et al (2021) compared the gut microbiota and MQTs of males and castrated Holstein cattle and found that castrated Holstein cattle had a higher relative abundance of the family Gastrostreptococcus and increased extra-and IMF storage. Another study compared the gut microbiota between grazing and feedlot Angus cattle and the authors speculated that the significant difference in gut microbiota composition in Angus cattle could affect the meat quality of Angus beef (Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%